2003
DOI: 10.1007/bf02785958
|View full text |Cite
|
Sign up to set email alerts
|

The gauss map on a class of interval translation mappings

Abstract: Abstract. We study the dynamics of a class of interval translation map on three intervals. We show that in this class the typical ITM is of finite type (reduce to an interval exchange transformation) and that the complement contains a Cantor set. We relate our maps to substitution subshifts. Results on Hausdorff dimension of the attractor and on unique ergodicity are obtained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 17 publications
0
49
0
3
Order By: Relevance
“…The term double rotations was introduced in [12], they have also been studied in [3], [4] and [5]. We show that up to a natural involution there exists a bijection between double rotations and billiard map we work with, and therefore almost all of our billiard map are of finite type due to the corresponding results for double rotations (Theorem 2.2 part 2) (see [12] and [5]).…”
Section: Introductionmentioning
confidence: 69%
“…The term double rotations was introduced in [12], they have also been studied in [3], [4] and [5]. We show that up to a natural involution there exists a bijection between double rotations and billiard map we work with, and therefore almost all of our billiard map are of finite type due to the corresponding results for double rotations (Theorem 2.2 part 2) (see [12] and [5]).…”
Section: Introductionmentioning
confidence: 69%
“…Similar to [2], we prove the following theorem. Theorem 1.1: Let A d be the set of parameters such that T is of type 1.…”
Section: Introductionmentioning
confidence: 87%
“…Boshernitzan and Kornfeld showed, using a renormalization operator, that a specific ITM has an attracting Cantor set. Bruin and Troubetzkoy [2] extended this result to a 2-parameter family of ITMs with three pieces (or two pieces when considered on the circle), and showed that type 1 maps occur for an uncountable set of Lebesgue measure 0 in parameter space. In [3], it is shown that type 1 occurs with Lebesgue measure 0 in the full 3-parameter family of 2-piece ITMs on the circle.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…История вопроса. Первоначально двухцветные сдвиги S (α,β,ε) (x) по-явились в работах [3], [4] и затем в общем виде (0.1) -в [2]. Двухцветные сдви-ги представляют собою частный случай IT-отображений (interval translation mappings [3]).…”
Section: Introductionunclassified